Assessment of Regional Longitudinal Stain by Using Speckle Tracking Echocardiography – A Validation Study - Nili, Vitek; Noa, Bachner-Hinenzon; Meytal, Lempel; Zvi, Friedman; Shimon, Reisner; Rafael, Beyar; Dan, Adam (IntechOpen, 2012)
None